HUBUNGAN HALUSINASI DENGAN KEJADIAN PERILAKU KEKERASAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT KHUSUS JIWA PROVINSI BENGKULU - Dilfera Hermiati; Ravika Ramlis (JURNAL PENELITIAN TERAPAN KESEHATAN, 2023)
There are around 450 million people with mental disorders in the world, including schizophrenia. The prevalence of schizophrenia in Indonesia has reached 400,000 people or as much as 1.7 per 1,000 population. Schizophrenia is a chronic mental disorder characterized by changes in thought processes, perceptions, behavior, and decreased social functioning. Some of these signs and symptoms will influence each other including hallucinations and violent behavior. The research objective was to determine the relationship between hallucinations and violent behavior in schizophrenic patients at the Special Mental Hospital in Bengkulu Province. The method in this study is a quantitative study using an analytic research design and a cross sectional design. The sample in this study was 78 respondents who were selected according to the inclusion and exclusion criteria. This study used the chi-square statistical test. The results of this study indicate that there are a small proportion of 20 (25.7%) who experience violent behavior and more than 45 (57.7%) who experience hallucinations. The results of the chi-square statistical test obtained a p value of 0.015 <0.05, meaning that there was a relationship between hallucinations and violent behavior in schizophrenic patients at the Special Mental Hospital in Bengkulu Province. The conclusion in this study is that hallucinatory symptoms in schizophrenic patients can lead to violent behavior. Suggestions in this study are that nurses should evaluate schizophrenic patients more in practicing how to deal with hallucinations so that violent behavior does not occur and intervene according to the signs and symptoms that arise Keywords: Schizophrenia, violent behavior, hallucinations